Compare Between Genetic Algorithm and Clonal Selection Algorithm To Pattern Recognition Latin's Numbers - Maha Mohammed (College of Education for Pure Sciences, 1970)
Abstract        This work involves the use  some of Artificial intelligence techniques algorithms which are genetic algorithm and artificial immune system algorithm- clonal selection algorithm.        A comparison was done between the original mode of the Latin number and the distorted modes applied for the same number and with the use of above algorithms.        Mode results obtained from implementing both algorithms showed that the artificial immune system algorithm(Clonal selection algorithm) was good and 85% in getting closer modes to that of the applied Latin number original mode.       Both above algorithms are based on optimization principle in getting the results.